Silver powder and preparation method and application thereof

By preparing silver powder with nano -structure, the problem of low existing silver powder sintering and poor printing performance has been solved, and high -efficiency sintering and excellent conductivity and printing performance are achieved. It is suitable for the metal application of solar cells.

CN119368756AActive Publication Date: 2025-01-28HA SHEN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411577402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-28
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The silver powder in the silver paste on the back of existing solar cells is large in size, has poor morphological regularity, and has low sintering activity, resulting in low conductivity and poor printing performance.

Method used

Prepare a silver powder with nano -micro -structure. Its grain size ≤150nm, the income rate is ≥11 %, and the sintering temperature corresponding to the maximum shrinkage rate ≤550 ° C. By mixing the nano -silver crystal solution with the dispersion agent, the reducing solution, and the surface regulator, then reacts with the front -drive body solution containing silver ions to achieve the nano -structural adjustment and control of the silver particles.

Benefits of technology

It improves the sintering performance of silver powder, realizes high -efficiency sintering at low temperatures, has better conductivity and printing performance, and meets the efficiency requirements of the surface metallicization of crystalline silicon solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368756A_ABST
    Figure CN119368756A_ABST
Patent Text Reader

Abstract

The invention discloses silver powder and a preparation method and application thereof, and belongs to the technical field of silver powder. The surface of the silver powder is provided with a nanometer microstructure, the grain size of the silver powder is smaller than or equal to 150 nm, the yield rate of the silver powder is larger than or equal to 11%, and the sintering temperature corresponding to the maximum shrinkage rate of the silver powder is smaller than or equal to 550 DEG C. The silver powder has the small grain size and high sintering activity, the temperature corresponding to the maximum shrinkage rate can be low while the high shrinkage rate is achieved, and therefore the good sintering performance is obtained, and the efficiency requirement for metallization of the surface of a crystalline silicon solar cell can be met. The preparation method of the silver powder is simple and easy to operate, and industrial production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silver powder, and in particular to silver powder and a preparation method and application thereof. Background Art

[0002] The silver paste on the back of solar cells is the main component of the electronic paste of solar cells. It is mainly used to make the back main grid in the production of solar cells, which plays the role of converging and conducting the current collected by the aluminum back field. The silver paste on the back of solar cells is mainly composed of silver powder, glass powder and organic carrier.

[0003] At present, conventional silver powder is mainly micron-sized, with large size, poor morphology regularity and low sintering activity, resulting in low conductivity of the material and poor printing performance.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a silver powder and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a silver powder having a nanostructure on its surface;

[0008] The grain size of the silver powder is ≤150nm, the shrinkage rate of the silver powder is ≥11%, and the sintering temperature corresponding to the maximum shrinkage rate of the silver powder is ≤550℃.

[0009] In an optional embodiment, the silver powder further comprises at least one of the following features:

[0010] Feature 1: The nanostructure includes at least one of a block structure, a sheet structure, a prism structure, a strip structure, a rod structure, a spherical structure, a pore structure and a hole structure at the nanoscale;

[0011] Feature 2: The specific surface area of ​​silver powder is 0.4m 2 / g~1.1m 2 / g;

[0012] Feature 3: The burnout of silver powder is 0.4% to 1.5%;

[0013] Feature 4: Silver powder D 10 0.7μm~1.7μm;

[0014] Feature 5: Silver powder D 50 1.1μm~3.2μm;

[0015] Feature 6: Silver powder D 90It is 1.7μm~5.8μm.

[0016] In a second aspect, the present invention provides a method for preparing silver powder as described in the aforementioned embodiment, comprising the following steps: mixing a nano silver seed solution with a dispersant to obtain a first mixed solution; mixing the first mixed solution with a reducing solution and a surface conditioner solution to obtain a second mixed solution; and mixing the second mixed solution with a precursor solution containing silver ions for reaction.

[0017] In an optional embodiment, the particle size of the nanosilver seeds in the nanosilver seed solution is 10 nm to 80 nm;

[0018] and / or, the mass fraction of the nano-silver seeds in the nano-silver seed solution is 0.1% to 5%;

[0019] and / or, the shape of the nano silver seed crystal is spherical;

[0020] And / or, the concentration of silver ions in the precursor solution containing silver ions is 0.5 mol / L to 2.5 mol / L.

[0021] In an optional embodiment, the dispersant includes at least one of gum arabic, gelatin, polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone and Tween;

[0022] And / or, the amount of the dispersant used is 0.5% to 20% of the mass of the silver ions in the precursor solution containing silver ions, preferably 5% to 10%.

[0023] In an optional embodiment, the concentration of the reducing agent contained in the reducing solution is 0.2 mol / L to 2.0 mol / L;

[0024] and / or, the reducing agent contained in the reducing solution includes at least one of ascorbic acid, glucose, isoascorbic acid, sodium isoascorbate, sodium ascorbate and sodium gluconate;

[0025] And / or, based on the theoretical molar ratio of electrons transferred in the reaction between the reducing agent and the silver ions, the molar ratio of the reducing agent contained in the reducing solution to the silver ions in the precursor solution containing the silver ions is 1.02:1 to 2.0:1.

[0026] In an alternative embodiment, the surface conditioning agent solution is an organic conditioning agent containing a carboxylic acid functional group;

[0027] and / or, the mass fraction of the surface conditioner in the surface conditioner solution is 0.5% to 10%;

[0028] And / or, the mass of the surface conditioner in the surface conditioner solution is 0.1% to 5% of the mass of the silver ions in the precursor solution containing silver ions.

[0029] In an optional embodiment, when the temperature of the mixed reaction is 15°C to 40°C, the surface regulator is a carboxylic acid substance with a carbon number of ≤8; when the temperature of the mixed reaction exceeds 40°C and does not exceed 60°C, the surface regulator is a fatty acid substance with a carbon number of ≥12.

[0030] In an optional embodiment, when the temperature of the mixed reaction is 15°C to 40°C, the surface regulator includes at least one of malonic acid, acrylic acid, succinic acid, fumaric acid, succinic acid, malic acid, maleic acid, citric acid, tartaric acid, sorbic acid and mandelic acid; when the temperature of the mixed reaction exceeds 40°C and does not exceed 60°C, the surface regulator includes at least one of lauric acid, myristic acid, palmitic acid, oleic acid, 731A and polyacrylic acid.

[0031] In an optional embodiment, the temperature of the mixing reaction is 15° C. to 60° C.; and the time of the mixing reaction is 5 min to 20 min.

[0032] In an optional embodiment, a precursor solution containing silver ions is added to the second mixed solution to perform a mixing reaction.

[0033] In an optional embodiment, the precursor solution containing silver ions is added to the second mixed solution within 15 seconds.

[0034] In an optional embodiment, the method further comprises: coating the solid matter obtained from the mixed reaction.

[0035] In an optional embodiment, the coating process includes: mixing the solid object with a coating liquid.

[0036] In an optional embodiment, the mass fraction of the coating agent contained in the coating liquid is 10% to 40%.

[0037] In an optional embodiment, the solution contained in the coating liquid is water and / or alcohol.

[0038] In an optional embodiment, the amount of the coating agent used is 0.1% to 5% of the mass of the silver ions in the precursor solution containing silver ions.

[0039] In a third aspect, the present invention provides use of the silver powder according to the aforementioned embodiment in preparing a solar cell.

[0040] The beneficial effects of the present invention include:

[0041] The present invention provides silver powder with a nanostructure on the surface. The silver powder has a small grain size and has excellent sintering performance, such as high sintering activity, which can be sintered at a lower temperature, and has a high shrinkage rate while making the temperature corresponding to the maximum shrinkage rate lower. The silver powder also has good conductivity and printing performance, and can meet the efficiency requirements of surface metallization of crystalline silicon solar cells.

[0042] The present invention provides a method for preparing silver powder, wherein the first mixed solution is used as a reaction base solution, and the seed crystal can be used as a site for heterogeneous nucleation during the preparation of silver to obtain silver particles with narrow size distribution and uniform dispersion. The reducing agent in the reducing solution is used to reduce the silver ions in the silver nitrate to silver element; the surface conditioning agent solution can adjust and control the surface nanostructure of the silver particles in combination with the reaction temperature and the material addition time; and the precursor solution containing silver ions is used to react with the reducing agent. This method can effectively obtain silver powder with a nano-microstructure on the surface, a grain size of ≤150nm, a shrinkage rate of ≥11%, and a sintering temperature of ≤550°C corresponding to the maximum shrinkage rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 This is a SEM image of the silver powder product prepared in Example 1;

[0045] Figure 2 This is a SEM image of the silver powder product prepared in Example 2;

[0046] Figure 3 This is a SEM image of the silver powder product prepared in Example 3;

[0047] Figure 4 This is a SEM image of the silver powder product prepared in Example 4;

[0048] Figure 5 This is a SEM image of the silver powder product prepared in Example 5;

[0049] Figure 6 This is a SEM image of the silver powder product prepared in Example 6;

[0050] Figure 7 This is a SEM image of the silver powder product prepared in Example 7;

[0051] Figure 8 This is a SEM image of the silver powder product prepared in Example 8;

[0052] Fig. 9 This is a SEM image of the silver powder product prepared in Example 9;

[0053] Fig.10This is a SEM image of the silver powder product prepared in Example 10;

[0054] Fig.11 This is a SEM image of the silver powder product prepared in Example 11;

[0055] Fig.12 This is a SEM image of the silver powder product prepared in Comparative Example 1;

[0056] Fig.13 This is the SEM image of the silver powder product prepared in Comparative Example 2;

[0057] Fig.14 This is a SEM image of the silver powder product prepared in Comparative Example 3;

[0058] Fig.15 This is a SEM image of the silver powder product prepared in Comparative Example 4;

[0059] Fig.16 This is a SEM image of the silver powder product prepared in Comparative Example 5;

[0060] Fig.17 This is a SEM image of the silver powder product prepared in Comparative Example 6;

[0061] Fig.18 It is the inverse pole figure of the silver powder product corresponding to Example 1 in the test example;

[0062] Fig.19 It is the inverse pole figure of the silver powder product corresponding to Comparative Example 3 in the test example;

[0063] Fig. 20 It is a TMA test shrinkage curve diagram of the silver powder products corresponding to Example 1, Example 2, Comparative Example 1 and Comparative Example 2 in the test examples;

[0064] Fig.21 It is a TMA test shrinkage rate curve diagram of the silver powder products corresponding to Example 1 and Comparative Example 1 in the test example. DETAILED DESCRIPTION

[0065] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0066] The silver powder provided by the present invention and its preparation method and application are described in detail below.

[0067] The present invention provides a silver powder, the surface of which has a nanostructure;

[0068] The grain size of the silver powder is ≤150nm, the shrinkage rate of the silver powder is ≥11%, and the sintering temperature corresponding to the maximum shrinkage rate of the silver powder is ≤550°C.

[0069] The above-mentioned "nano-microstructure" refers to a microstructure at the nanoscale, wherein the "microstructure" may include at least one of a block structure, a sheet structure, a prism structure, a strip structure, a rod structure, a spherical structure, a pore structure and a hole structure by way of example but not limitation. In a specific embodiment, the silver powder may have only any one of the above-mentioned specific structures, or may contain two or more of the above-mentioned specific structures at the same time. Furthermore, when the surface of the silver powder contains two or more microstructures, each microstructure may exist independently, or may be a composite structure formed by rotation, winding, combination, etc.

[0070] The nanostructure on the surface of the silver powder can improve the sintering performance of the silver particles, achieve sintering at a lower temperature, and meet the efficiency requirements of the surface metallization of crystalline silicon solar cells.

[0071] In the present invention, the grain size of the silver powder is obtained by testing using an EBSD device, and the grain size does not exceed 150 nm, for example, it can be 130 nm to 150 nm, such as 132.2 nm, 135.2 nm, 135.8 nm, 139.1 nm, 141.9 nm, 144.9 nm, 145.3 nm, 147.5 nm, 147.7 nm, 148.1 nm or 148.8 nm, or it can be other values ​​within the range of 130 nm to 150 nm.

[0072] In some optional embodiments, the specific surface area of ​​the silver powder is 0.4 m 2 / g~1.1m 2 / g, such as 0.411m 2 / g, 0.414m 2 / g, 0.438m 2 / g, 0.537m 2 / g, 0.691m 2 / g, 0.814m 2 / g, 0.822m 2 / g, 0.841m 2 / g, 0.894m 2 / g, 0.924m 2 / g or 1.037m 2 / g, etc., can also be 0.4m 2 / g~1.1m 2 / Other values ​​within the range of g.

[0073] In the present invention, the recovery rate of silver powder is not less than 11%, for example, it can be 12% to 18.5%, such as 12.11%, 14.21%, 14.48%, 14.97%, 15.42%, 15.82%, 16.13%, 16.40%, 16.79%, 17.13% or 18.33%, etc., and can also be other values ​​within the range of 12% to 18.5%.

[0074] Moreover, the sintering temperature corresponding to the maximum shrinkage rate of the silver powder is ≤550°C, for example, it can be 495°C to 550°C, such as 498°C, 506°C, 511°C, 512°C, 533°C, 536°C, 539°C, 544°C, 545°C or 549°C, or it can be other values ​​within the range of 495°C to 550°C.

[0075] That is, the silver powder provided by the present invention has a high sintering activity and can have a high shrinkage rate while making the temperature corresponding to the maximum shrinkage rate low.

[0076] In some optional embodiments, the silver powder has a burnout of 0.4% to 1.5%. In some typical embodiments, the silver powder has a burnout of 0.5% to 1.3%, such as 0.52%, 0.68%, 0.71%, 0.84%, 0.88%, 0.91%, 0.92%, 0.93%, 1.17% or 1.24%, etc., and may also be other values ​​within the range of 0.5% to 1.3%.

[0077] In some optional embodiments, the silver powder has a D 10 It can be 0.7 μm to 1.7 μm. In some typical embodiments, the D 10 It can be 0.7437μm to 1.691μm.

[0078] In some optional embodiments, the silver powder has a D 50 In some typical embodiments, the D 50 1.1052μm~3.148μm;

[0079] In some optional embodiments, the silver powder has a D 90 In some typical embodiments, the D 90 It is 1.7445μm~5.610μm.

[0080] The silver powder with the above-mentioned particle size has regular morphology and uniform size, which is beneficial to improving the sintering performance of the silver powder.

[0081] As mentioned above, silver powder has a smaller grain size, and its main structure is spherical or quasi-spherical, and the particle size and particle size distribution are within a suitable range, so that the obtained silver powder product has a moderate specific surface area, and has excellent printability and high sintering activity in application. On the other hand, the nano-microstructure on the surface of the silver powder can further improve the sintering activity of the silver particles.

[0082] Correspondingly, the present invention also provides a method for preparing the above-mentioned silver powder, comprising the following steps: mixing a nano silver seed solution with a dispersant to obtain a first mixed solution; mixing the first mixed solution with a reducing solution and a surface conditioner solution to obtain a second mixed solution; and mixing the second mixed solution with a precursor solution containing silver ions for reaction.

[0083] Among them, the first mixed solution is used as the reaction base solution, and the seed crystal can be used as a site for heterogeneous nucleation in the process of preparing silver, so as to obtain silver particles with narrow size distribution and uniform dispersion. The reducing agent in the reducing solution is a substance that reduces the silver ions in silver nitrate to silver element; the surface conditioning agent solution is obtained by dissolving the surface conditioning agent in water, and the reaction temperature and material addition time can be used to adjust and control the surface nanostructure of the silver particles; the precursor solution containing silver ions is used to react with the reducing agent.

[0084] In some optional embodiments, the shape of the nano silver seed is spherical. The particle size of the nano silver seed in the nano silver seed solution is 10nm to 80nm, such as 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm or 80nm, etc., and can also be other values ​​within the range of 10nm to 80nm.

[0085] The mass fraction of the nanosilver seeds in the nanosilver seed solution can be 0.1% to 5%, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or other values ​​within the range of 0.1% to 5%.

[0086] In some optional embodiments, the dispersant may illustratively but not limitatively include at least one of gum arabic, gelatin, polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone and Tween.

[0087] The amount of the dispersant can be 0.5% to 20% of the mass of the silver ions in the precursor solution containing silver ions, such as 0.5%, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, etc., or other values ​​within the range of 0.5% to 20%. In some preferred embodiments, the amount of the dispersant can be 5% to 10% of the mass of the silver ions in the precursor solution containing silver ions, such as 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc.

[0088] The precursor solution containing silver ions can be obtained by dissolving a silver source in water. The silver source can include silver nitrate, etc., by way of example but not limitation. The concentration of silver ions in the precursor solution containing silver ions can be 0.5 mol / L to 2.5 mol / L, such as 0.5 mL / min, 1.0 mL / min, 1.5 mL / min, 2.0 mL / min or 2.5 mL / min, etc., or other values ​​within the range of 0.5 mol / L to 2.5 mol / L.

[0089] In some optional embodiments, the concentration of the reducing agent contained in the reducing solution can be 0.2mol / L to 2.0mol / L, such as 0.2mol / L, 0.5mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L or 2mol / L, etc., or it can be other values ​​within the range of 0.2mol / L to 2.0mol / L.

[0090] The reducing agent contained in the reducing solution may illustratively but not limitatively include at least one of ascorbic acid, glucose, erythorbic acid, sodium erythorbic acid, sodium ascorbate, sodium ascorbate and sodium gluconate.

[0091] Based on the theoretical molar ratio of electrons transferred in the reaction between the reducing agent and the silver ions, the molar ratio of the reducing agent contained in the reducing solution to the silver ions in the silver ion-containing precursor solution can be 1.02:1 to 2.0:1, such as 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, 1.0:1, 1.2:1, 1.5:1, 1.8:1 or 2.0:1, or other values ​​within the range of 1.02:1 to 2.0:1.

[0092] In some alternative embodiments, the surface conditioner solution is an organic conditioner containing carboxylic acid functional groups.

[0093] The mass fraction of the surface conditioner in the surface conditioner solution can be 0.5% to 10%, such as 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., or other values ​​within the range of 0.5% to 10%.

[0094] The mass of the surface conditioner in the surface conditioner solution can be 0.1% to 5% of the mass of the silver ions in the silver ion-containing precursor solution, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be other values ​​within the range of 0.1% to 5%.

[0095] In some optional embodiments, the first mixed solution, the reducing solution and the surface conditioning agent solution can be mixed under stirring conditions (the stirring speed can be 200 r / min) for 1 min to 10 min (such as 1 min, 2 min, 5 min, 8 min or 10 min, etc.) to obtain a second mixed solution. Subsequently, the precursor solution containing silver ions is quickly added to the second mixed solution for reaction.

[0096] In some optional embodiments, the temperature of the mixing reaction can be 15°C to 60°C, such as 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, etc., or other values ​​within the range of 15°C to 60°C.

[0097] The time of the mixing reaction can be 5 min to 20 min, such as 5 min, 10 min, 15 min or 20 min, etc., or other values ​​within the range of 5 min to 20 min.

[0098] When the temperature of the mixing reaction is 15°C to 40°C, the surface regulator is a carboxylic acid substance with a carbon number ≤8, and illustratively may include at least one of malonic acid, acrylic acid, succinic acid, fumaric acid, succinic acid, malic acid, maleic acid, citric acid, tartaric acid, sorbic acid and mandelic acid.

[0099] When the temperature of the mixing reaction exceeds 40°C and does not exceed 60°C, the surface regulator is a fatty acid substance with a carbon number ≥ 12, and illustratively may include at least one of lauric acid, myristic acid, palmitic acid, oleic acid, 731A (polycarboxylic acid) and polyacrylic acid.

[0100] It should be noted that different reaction temperature conditions require surfactants containing carboxylic acids with different carbon atoms to adjust the surface structure of silver particles. The C=O bond in the carboxylic acid has an adsorption effect with silver ions or silver atoms. In the late stage of the reaction when the secondary silver particles are stable, the adsorption of the C=O bond on the (111) surface of the silver atoms combined with the Oswald ripening effect makes the surface structure of the silver particles appear in nanosheets, plates, small particles and other structures. The diffusion rate of silver atoms that explode and nucleate in the low-temperature section is slow, and the driving force for aggregation and growth into secondary particles is weak. Therefore, short-chain carboxylic acids are required to avoid affecting the growth of aggregation, in order to achieve silver particles with a spherical structure. Therefore, when the reaction temperature is 15°C to 40°C, the present invention uses carboxylic acids with a carbon number of less than or equal to 8 as surface regulators; at high temperatures, the diffusion rate of silver atoms is fast, and diffusion growth and aggregation growth exist at the same time and the driving force is strong. Therefore, long-chain carboxylic acids are required to prevent the excessive diffusion growth of silver atoms in the process of adjusting the surface structure, so as to avoid serious agglomeration and enlargement of grain size. Therefore, when the reaction temperature exceeds 40°C and does not exceed 60°C, the present invention uses fatty acids with a carbon number of greater than or equal to 12 as surface regulators.

[0101] In some optional embodiments, the precursor solution containing silver ions is added to the second mixed solution for a mixing reaction. Preferably, the precursor solution containing silver ions is added to the second mixed solution within 15 seconds.

[0102] The precursor solution containing silver ions can be quickly added to the second mixed solution within 15 seconds (such as 1 second to 15 seconds) by means of gravity, injection pressure, etc., thereby realizing the synthesis of the nanostructure on the surface of the silver particles.

[0103] As mentioned above, the present invention achieves the acquisition and control of the surface nanostructure of silver particles through temperature, rapid mixing time and surface conditioning agent. Among them, nano silver seeds with a particle size of 10nm to 80nm can be used as sites for heterogeneous nucleation in the process of preparing silver, and silver particles with narrow size distribution and uniform dispersion are obtained. The use of seeds can inhibit the diffusion growth of silver particles under high supersaturation (silver ion precursor solution addition time <15s) during the preparation of silver particles, so that the grain size is less than 150nm, thereby improving the sintering activity of silver particles. Among them, the rapid addition of silver ions reacts instantly with the reducing agent, and the explosion nucleation on the surface of the seeds leads to a high supersaturation of silver atoms, and the short-term diffusion growth forms small-sized primary particles, which further aggregate and grow into secondary silver particles with a spherical structure under high supersaturation conditions. The spherical structure ensures that the silver particles have a suitable specific surface area, realizing basic applications in solar slurries.

[0104] Furthermore, the solid obtained by the mixed reaction can be coated. The coating process can be carried out in the final cleaning stage of the silver powder or in the drying, crushing or gas grinding stage.

[0105] In some optional embodiments, the coating process includes: mixing the solid object with a coating liquid.

[0106] The mass fraction of the coating agent contained in the coating solution may be 10% to 40%, such as 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., or other values ​​within the range of 10% to 40%.

[0107] The solution contained in the coating liquid may be water and / or alcohol.

[0108] In some optional embodiments, the amount of the capping agent can be 0.1% to 5% of the mass of silver ions in the silver ion-containing precursor solution, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be other values ​​within the range of 0.1% to 5%.

[0109] Furthermore, after the coating process, the coated material may be dried and crushed.

[0110] In addition, the present invention also provides the use of the silver powder in preparing solar cells.

[0111] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0112] Example 1

[0113] This embodiment provides a silver powder product, and the preparation method thereof includes:

[0114] S1: 30 g of silver nitrate and 118 g of deionized water are prepared into a precursor solution containing silver ions.

[0115] 19 g of ascorbic acid and 135 g of deionized water were prepared into a reducing solution, and the concentration of the reducing agent in the reducing solution was about 0.8 mol / L.

[0116] The spherical nano silver seeds and deionized water are mixed to form a nano silver seed solution, wherein the mass fraction of the nano silver seeds is 1.5% and the particle size of the nano silver seeds is 10nm-50nm.

[0117] S2: 380 μL of the nanosilver seed solution, 1.5 g of a dispersant (PVP) and 244 g of deionized water were mixed to obtain a first mixed solution.

[0118] The amount of the dispersant used is 7.87% of the mass of the silver ions in the precursor solution containing silver ions.

[0119] S3: Add the reducing solution and the surface conditioner solution (1.0 g of tartronic acid aqueous solution and 3.5 g of citric acid aqueous solution) to the first mixed solution, and stir and mix at a speed of 200 r / min for 5 minutes to obtain a second mixed solution.

[0120] Wherein, based on the theoretical molar ratio of transferred electrons in the reaction between the reducing agent and the silver ions, the molar ratio of the reducing agent contained in the reducing solution to the silver ions in the precursor solution containing the silver ions is 1.2:1.

[0121] The mass fraction of succinic acid in the succinic acid aqueous solution is 10%, the mass fraction of citric acid in the citric acid aqueous solution is 10%, and the mass of the surface conditioner in the surface conditioner solution is 2.36% of the mass of silver ions in the silver ion-containing precursor solution.

[0122] S4: maintaining the temperature of the reaction solution at 25° C., rapidly adding the precursor solution containing silver ions into the second mixed solution within 10 seconds, and reacting for 10 minutes to obtain silver powder.

[0123] S5: After the silver powder is washed and subjected to solid-liquid separation, 2.5 g of coating liquid (butyl carbitol solution) is used for coating treatment, followed by drying and crushing to obtain a silver powder product.

[0124] The mass fraction of the coating agent in the coating solution is 10%, and the amount of the coating agent used is 1.3% of the mass of the silver ions in the precursor solution containing silver ions.

[0125] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 1 As shown, the surface of the silver powder particles has an obvious nanostructure and has higher sintering performance.

[0126] Example 2

[0127] This embodiment provides a silver powder product, and the preparation method thereof includes:

[0128] S1: 50 g of silver nitrate and 197 g of deionized water are prepared into a precursor solution containing silver ions.

[0129] 31.5 g of ascorbic acid and 225 g of deionized water were prepared into a reducing solution, and the concentration of the reducing agent in the reducing solution was about 0.8 mol / L.

[0130] The spherical nano silver seeds are mixed with deionized water to form a nano silver seed solution, wherein the mass fraction of the nano silver seeds is 0.5% and the particle size of the nano silver seeds is 15nm-60nm.

[0131] S2: 750 μL of the nanosilver seed solution, 4.8 g of a dispersant (Tween) and 407 g of deionized water were mixed to obtain a first mixed solution.

[0132] The amount of the dispersant used is 15% of the mass of the silver ions in the precursor solution containing silver ions.

[0133] S3: Add the reducing solution and the surface conditioner solution (3.0 g of oleic acid aqueous solution and 0.5 g of polyacrylic acid aqueous solution) to the first mixed solution, and stir and mix at a speed of 200 r / min for 2 minutes to obtain a second mixed solution.

[0134] Wherein, based on the theoretical molar ratio of transferred electrons in the reaction between the reducing agent and the silver ions, the molar ratio of the reducing agent contained in the reducing solution to the silver ions in the precursor solution containing the silver ions is 1.2:1.

[0135] The mass fraction of oleic acid in the oleic acid aqueous solution is 10%, the mass fraction of polyacrylic acid in the polyacrylic acid aqueous solution is 10%, and the mass of the surface conditioner in the surface conditioner solution is 1.1% of the mass of silver ions in the silver ion-containing precursor solution.

[0136] S4: maintaining the temperature of the reaction solution at 45° C., rapidly adding the precursor solution containing silver ions into the second mixed solution within 15 seconds, and reacting for 10 minutes to obtain silver powder.

[0137] S5: After the silver powder is washed and subjected to solid-liquid separation, 2.5 g of coating liquid (butyl carbitol solution) is used for coating treatment, followed by drying and crushing to obtain a silver powder product.

[0138] The mass fraction of the coating agent in the coating solution is 10%, and the amount of the coating agent used is 0.79% of the mass of the silver ions in the precursor solution containing silver ions.

[0139] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 2 As shown, the surface of the silver powder particles is closed and has block-like protruding nanostructures.

[0140] Example 3

[0141] The difference between this example and example 1 is that the reducing agent in the reducing solution is replaced with 21.4 g of sodium isoascorbate to maintain the same electron transfer molar ratio.

[0142] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 3 As shown, there are ridge-like nanoplatelet structures on the surface of the silver powder particles.

[0143] Example 4

[0144] The difference between this embodiment and embodiment 1 is that the volume of the nanosilver seed solution is reduced to 250 μL.

[0145] This embodiment has fewer nucleation sites than embodiment 1, and the microstructure of the silver powder product prepared is as follows: Figure 4 As shown, there is a flaky and densely packed nanostructure on the surface of the silver powder particles.

[0146] Example 5

[0147] The difference between this embodiment and embodiment 1 is that the reaction temperature is 15°C.

[0148] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 5 As shown, there is a nanoporous structure on the surface of the silver powder particles.

[0149] Example 6

[0150] The difference between this embodiment and embodiment 1 is that the time for adding the precursor solution containing silver ions into the second mixed solution is 5 seconds.

[0151] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 6 As shown, there is a nanoparticle structure on the surface of the silver powder particles.

[0152] Example 7

[0153] The difference between this embodiment and embodiment 1 is that the surface conditioner solution is replaced by 2.23 g of 10% mass concentration sorbic acid aqueous solution and 0.56 g of 10% mass concentration maleic acid aqueous solution.

[0154] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 7 As shown, there is a nano-block structure on the surface of the silver powder particles.

[0155] Example 8

[0156] The difference between this embodiment and embodiment 1 is that 2.5 g of Tween and 1.3 g of polyvinyl alcohol are used as the dispersant.

[0157] The microstructure of the silver powder product prepared in this embodiment is as follows Figure 8 As shown, there are nano-block structures on the surface of silver powder particles.

[0158] Example 9

[0159] The difference between this embodiment and embodiment 2 is that the surface conditioner solution is replaced by 3.5 g of 10% mass concentration lauric acid aqueous solution and 0.65 g of 10% mass concentration 731A aqueous solution.

[0160] The microstructure of the silver powder product prepared in this embodiment is as follows Fig. 9 As shown, there is a nanosheet stacking structure on the surface of the silver powder particles.

[0161] Example 10

[0162] The difference between this embodiment and embodiment 2 is that the dispersant is replaced by 1.2 g of gum arabic and 2.5 g of PVP.

[0163] The microstructure of the silver powder product prepared in this embodiment is as follows Fig.10 As shown, there are large nanosheet structures on the surface of silver powder particles.

[0164] Embodiment 11

[0165] The difference between this embodiment and embodiment 2 is that the reaction temperature is 60°C.

[0166] The silver particles prepared in this embodiment are relatively large in size and have slightly poor sintering activity.

[0167] The microstructure of the silver powder product prepared in this embodiment is as follows Fig.11 As shown, there is a nanostructure on the surface of the silver powder particles, but there is an agglomeration effect.

[0168] Comparative Example 1

[0169] The difference between this comparative example and Example 1 is that the time for adding the silver ion-containing precursor solution into the second mixed solution is 30 seconds.

[0170] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.12 As shown, due to the increase in the time of adding silver ions, the concentration of silver atoms generated per unit time in the reaction decreases, that is, the supersaturation decreases, the aggregation characteristics of the generated silver powder particles are weakened, and the silver particles are plate-like, flaky, and mixed block structures. However, the morphology of the silver powder particles obtained in this comparative example is not spherical or quasi-spherical, the specific surface area and particle size of each silver powder particle vary greatly, the tap density is low, and the printing performance is poor, which makes it difficult to be used in solar slurry applications.

[0171] Comparative Example 2

[0172] The difference between this comparative example and Example 1 is that the surface regulator used therein is 3.8 g of myristic acid having a carbon number ≥ 12.

[0173] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.13 As shown, there is a nano-flake microstructure on the surface of the silver powder particles, but the monodispersity of the silver particles is poor, and there are obvious large and small particles.

[0174] Comparative Example 3

[0175] The difference between this comparative example and Example 2 is that the surface regulators used are 1.2 g of succinic acid having a carbon number ≤ 8 and 2.67 g of malic acid.

[0176] During the preparation of this comparative example, the high temperature reaction causes the silver atoms to diffuse quickly, and the carboxylic acid with a low carbon number has a low effect on preventing the agglomeration of silver atoms. It is easy to cause the agglomeration of silver particles under high supersaturation, thereby reducing the sintering performance of the silver powder.

[0177] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.14 As shown, the silver powder particles have a smooth surface and less microstructure.

[0178] Comparative Example 4

[0179] The difference between this comparative example and Example 2 is that no seed crystal is used.

[0180] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.15 As shown, since no seed crystals were used, the particle size of the prepared silver powder was significantly increased.

[0181] Comparative Example 5

[0182] The difference between this comparative example and Example 2 is that the time for adding the precursor solution containing silver ions into the second mixed solution is 30 seconds.

[0183] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.16 As shown, the silver powder particles have a disordered structure, which may be due to the fact that low supersaturation leads to the diffusion growth effect of silver atoms, and the surface structure grows significantly. The silver powder particles prepared in this comparative example have poor sintering activity and poor printability, and are difficult to be used in solar slurry.

[0184] Comparative Example 6

[0185] The difference between this comparative example and Example 1 is that no surface conditioner is used.

[0186] The microstructure of the silver powder product prepared in this comparative example is as follows Fig.17 As shown, the surface of the silver powder particles is smooth, there is no surface nanostructure, the particles are relatively agglomerated, and have a polyhedral structure. The sintering performance of the silver powder particles is poor.

[0187] Test example

[0188] The silver powder products prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were compared, and the results are shown in Table 1.

[0189] Among them, particle size distribution: tested by laser particle size analyzer;

[0190] Test of the grain size of silver particles: Use a focused ion beam to cut the silver particles to obtain the cross-sectional structure, use electron backscatter diffraction to test the EBSD characterization information of the silver particle cross-section and calculate the grain size;

[0191] Shrinkage rate: The test was conducted using a thermomechanical analyzer (TMA). Specifically, 0.5 g of silver powder was pressed into a cylinder with a diameter of 6 mm under a pressure of 125 kgf using a tablet press. The shrinkage rate and shrinkage rate of the cylindrical sintered body as the temperature increased were tested to characterize the sintering properties of the silver powder itself.

[0192] Specific surface area: Anton Paar's specific surface area instrument was used for testing. Specifically, a nitrogen adsorption-desorption test was performed after degassing at 150°C for 30 minutes.

[0193] Burn-out: 3.0 g of silver powder was heated to 538°C in a muffle furnace for 1 hour, and the mass loss ratio was measured to obtain the burn-out data.

[0194] Taking Example 1 and Comparative Example 3 as examples, the grain size is compared, and the inverse pole figures obtained by EBSD test are compared. Fig.18 and Fig.19 shown. Fig.18 The reverse pole figure of the silver particles obtained in Example 1 was tested and statistically analyzed, and its grain size was 135.8 nm. Fig.19 This is the reverse pole figure of the silver particles obtained in Comparative Example 3, and the grain size thereof is tested to be 271.5 nm. It can be seen that the grain size of Comparative Example 3 is obviously too large.

[0195] Taking Example 1, Example 2, Comparative Example 1 and Comparative Example 4 as examples, the corresponding TMA test shrinkage curves are as follows: Fig. 20 As shown in FIG. 1 , the results show that the silver powder prepared in a manner other than the present invention has a small shrinkage rate and poor sintering activity. The shrinkage rate curves of Example 1 and Comparative Example 1 are shown in FIG. Fig.21 As shown, it can be seen that the silver powder obtained in Example 1 reaches a maximum shrinkage rate at about 497°C as the temperature increases, while the temperature corresponding to the maximum shrinkage rate of the silver powder obtained in Comparative Example 1 is 583°C, which proves that the silver powder obtained in Example 1 of the present invention has higher sintering activity than that in Comparative Example 1 and shrinks faster during the temperature increase process.

[0196] Table 1 Test results

[0197]

[0198]

[0199] As can be seen from Table 1, the silver powder provided in the embodiment of the present invention has a small grain size, a moderate specific surface area and a high sintering activity, and can have a high shrinkage rate while making the temperature corresponding to the maximum shrinkage rate low. In addition, the silver powder provided in this embodiment has good printability and a low burning loss value, and has better comprehensive performance than the silver powder prepared in the comparative example, and can better meet the application in the slurry.

[0200] In addition, conductivity comparison was performed using Example 1 and Comparative Example 1 as examples: 4.45 g of silver particles obtained in Example 1 and Comparative Example 1 were used as conductive phases. 0.15 g of tributyl citrate and 0.175 g of diethylene glycol butyl ether acetate were mixed as a bonding phase. 0.15 g of DBE solvent and 0.075 g of dimethyl silicone oil were mixed evenly with the silver particles and the bonding phase, and ground 5 times using a three-roll grinder to obtain a precision silver paste. After the silver paste was printed and cured, its resistivity was tested using a resistivity tester, which was 2.28 × 10 -8 Ω·m and 1.38×10 -7 Ω·m, it can be seen that the resistivity of the silver powder prepared in Example 1 of the present invention is significantly lower than that in Comparative Example 1.

[0201] In summary, the present invention realizes the surface nanostructure of silver particles by using surface regulator carboxylic acid substances with different carbon atoms and different temperatures; by controlling the addition time of the precursor solution containing silver ions to not exceed 15s, a high degree of supersaturation can be achieved to obtain silver particles with a spherical structure to achieve control of the specific surface area; by using seed crystals to control the final size of the silver particles, silver particles with good dispersibility, moderate size and surface microstructure can be obtained. The silver powder provided by the present invention has a smaller grain size and higher sintering activity. It can make the temperature corresponding to the maximum shrinkage rate lower while having a higher shrinkage rate, thereby obtaining better sintering performance and meeting the efficiency requirements of surface metallization of crystalline silicon solar cells. The preparation method of the silver powder is simple, easy to operate, and can be industrially produced.

[0202] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silver powder, characterized in that: The surface of the silver powder has a nanostructure; The grain size of the silver powder is ≤150nm, the shrinkage rate of the silver powder is ≥11%, and the sintering temperature corresponding to the maximum shrinkage rate of the silver powder is ≤550°C.

2. The silver powder according to claim 1, characterized in that The silver powder also includes at least one of the following features: Feature 1: The nano-microstructure includes at least one of a nanoscale block structure, a sheet structure, a prism structure, a strip structure, a rod structure, a spherical structure, a pore structure and a hole structure; Feature 2: The specific surface area of ​​the silver powder is 0.4m 2 / g~1.1m 2 / g; Feature 3: The burnout of the silver powder is 0.4% to 1.5%; Feature 4: The D of the silver powder 10 0.7μm~1.7μm; Feature 5: The D of the silver powder 50 1.1μm~3.2μm; Feature 6: The D of the silver powder 90 It is 1.7μm~5.8μm.

3. A method for preparing the silver powder according to claim 1 or 2, characterized in that: The following steps are involved: Mixing the nano silver seed solution with a dispersant to obtain a first mixed solution; Mixing the first mixed solution with a reducing solution and a surface conditioner solution to obtain a second mixed solution; The second mixed solution is mixed with a precursor solution containing silver ions for reaction.

4. The preparation method according to claim 3, characterized in that: The particle size of the nano-silver seeds in the nano-silver seed solution is 10nm to 80nm; And / or, the mass fraction of the nano-silver seeds in the nano-silver seed solution is 0.1% to 5%; And / or, the shape of the nano silver seed is spherical; And / or, the silver ion concentration in the silver ion-containing precursor solution is 0.5 mol / L to 2.5 mol / L.

5. The preparation method according to claim 3, characterized in that: The dispersant comprises at least one of gum arabic, gelatin, polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone and Tween; And / or, the amount of the dispersant used is 0.5% to 20% of the mass of the silver ions in the silver ion-containing precursor solution, preferably 5% to 10%.

6. The preparation method according to claim 3, characterized in that: The concentration of the reducing agent contained in the reducing solution is 0.2 mol / L to 2.0 mol / L; and / or, the reducing agent contained in the reducing solution includes at least one of ascorbic acid, glucose, isoascorbic acid, sodium isoascorbate, sodium ascorbate and sodium gluconate; And / or, based on the theoretical molar ratio of electrons transferred in the reaction between the reducing agent and the silver ions, the molar ratio of the reducing agent contained in the reducing solution to the silver ions in the silver ion-containing precursor solution is 1.02:1 to 2.0:

1.

7. The preparation method according to claim 3, characterized in that: The surface conditioning agent solution is an organic conditioning agent containing a carboxylic acid functional group; And / or, the mass fraction of the surface conditioner in the surface conditioner solution is 0.5% to 10%; and / or, the mass of the surface conditioner in the surface conditioner solution is 0.1% to 5% of the mass of the silver ions in the silver ion-containing precursor solution; Preferably, when the temperature of the mixed reaction is 15°C to 40°C, the surface conditioning agent is a carboxylic acid substance with a carbon number of ≤8; when the temperature of the mixed reaction exceeds 40°C and does not exceed 60°C, the surface conditioning agent is a fatty acid substance with a carbon number of ≥12; More preferably, when the temperature of the mixed reaction is 15°C to 40°C, the surface regulator includes at least one of malonic acid, acrylic acid, succinic acid, fumaric acid, succinic acid, malic acid, maleic acid, citric acid, tartaric acid, sorbic acid and mandelic acid; when the temperature of the mixed reaction exceeds 40°C and does not exceed 60°C, the surface regulator includes at least one of lauric acid, myristic acid, palmitic acid, oleic acid, 731A and polyacrylic acid.

8. The preparation method according to claim 3, characterized in that: The temperature of the mixed reaction is 15°C to 60°C; the time of the mixed reaction is 5min to 20min; Preferably, a precursor solution containing silver ions is added to the second mixed solution to perform a mixing reaction; More preferably, the precursor solution containing silver ions is added to the second mixed solution within 15 seconds.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The method also includes: coating the solid matter obtained from the mixed reaction; Preferably, the coating treatment comprises: mixing the solid object with a coating liquid; Preferably, the mass fraction of the coating agent contained in the coating solution is 10% to 40%; Preferably, the solution contained in the coating solution is water and / or alcohol; Preferably, the amount of the coating agent is 0.1% to 5% of the mass of the silver ions in the silver ion-containing precursor solution.

10. Use of the silver powder according to claim 1 or 2 in preparing solar cells.

Citation Information

Patent Citations

  • Silver particles and a process for making them

    CN102413967A

  • Preparation method for crystalline silicon photovoltaic cell front electrode silver paste

    CN110033875A

  • Silver particles and manufacturing method therefor

    CN110997198A

  • Water-soluble powdery precious metal nano material as well as preparation method and application thereof

    CN115592111A

  • Preparation method of polycrystalline structure silver particles, silver particles and silver paste

    CN118357471A

Cited By

  • Monodisperse spherical silver powder with smooth surface as well as preparation method and application of monodisperse spherical silver powder

    CN121423592A